Characterization and Chondroprotective Effects of Extracellular Vesicles From Plasma- and Serum-Based Autologous Blood-Derived Products for Osteoarthritis Therapy - Otahal, Alexander; Kramer, Karina; Kuten-Pella, Olga; Weiss, René; Stotter, Christoph; Lacza, Zsombor; Weber, Viktoria; Nehrer, Stefan; De Luna, Andrea (Frontiers in Bioengineering and Biotechnology, 2020)
Autologous blood products gain increasing interest in the field of regenerative medicine as well as in orthopaedics, aesthetic surgery and cosmetics. Currently, citrate-anti-coagulated platelet-rich plasma (CPRP) preparations are often applied in osteoarthritis (OA), but more physiological and cell-free alternatives such as hyperacute serum (hypACT) are under development. Beside growth factors, blood products also bring along extracellular vesicles (EVs) packed with signal molecules which opens up a new level of complexity at evaluating the functional spectrum of blood products. Large proportions of EVs originated from platelets in CPRP and hypACT, while very low erythrocyte and monocyte-derived EVs were detected via flow cytometry. EV treatment of chondrocytes enhanced the expression of anabolic markers type II collagen (COL2A1), SRY-box transcription factor 9 (SOX9) and aggrecan (ACAN) compared to full blood products, but also the catabolic marker and tissue remodeling factor matrix metalloproteinase 3 (MMP3), while hypACT EVs prevented type I collagen (COL1A1) expression. CPRP blood product increased SOX9 protein expression, in contrast to hypACT blood product. However, hypACT EVs induced SOX9 protein expression while preventing IL6 secretion. The results indicate that blood EVs are sufficient to induce chondrogenic gene expression changes in OA chondrocytes, while preventing pro-inflammatory cytokine release compared to full blood product. This highlights the potential of autologous blood-derived EVs as regulators of cartilage extracellular matrix metabolism and inflammation as well as candidates for new cell-free therapeutic approaches for OA.